EASTERN INTELLECTUAL FOUNDATIONS OF INCLUSIVE SOCIAL SUPPORT: DISABILITY, JUSTICE AND PUBLIC RESPONSIBILITY (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This thesis analyzes social support for persons with disabilities in the intellectual heritage of Eastern thinkers, jurists, and statesmen. The study shows that the treatment of vulnerable groups was understood as a criterion of justice, moral maturity, and responsible governance. Drawing on Islamic jurisprudence, moral philosophy, and public administration, the thesis highlights legal recognition, compassion, material assistance, labor inclusion, tax relief, and protection from oppression. The main argument is that persons with disabilities were not presented as people outside society, but as individuals whose dignity, rights, and needs had to remain at the center of social attention.